Pluralism and Populism in the Bulgarian Party System: Connections and Contradictions - Asenov, Simeon (Research Papers, 2022)
The paper examines the role of political pluralism for transformations and the rise of populism in the Bulgarian party system. The populism dimensions are analysed in legal and political aspect. The paper also depicts the contradictory relation between pluralism and populism in politics. Conclusions are made for their coexistence and impact on the political party system and democratic process in our country. In methodological aspect, the paper uses the political and legal analysis of the researched issue.
Keywords: Parties; Political pluralism; Party system; Populism